(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Morphometric measurements and meristic counts of Coilia ramcarati (Hamilton, 1822) were analysed statistically to ascertain the possible racial difference in the species from Chittagong and Coxs Bazar coasts of the Bay of Bengal. Some variations were found (insignificant, p ? 0.05), indicating that the populations of C. ramcarati from Chittagong and Coxs Bazar coasts are not racially differentiated. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20213 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 71-74, 2014